2019
DOI: 10.1002/mame.201900137
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Insulation Characteristics of Polybenzoxazine Aerogels

Abstract: Polybenzoxazine (PBO) aerogels with low densities and low thermal conductivities are prepared from Bisphenol A (BPA) benzoxazine monomers by ring‐opened polymerisation using HCl as a catalyser at 10 °C. The obtained PBO aerogels have cross‐linked and 3D network structures with the densities ranging from 0.084 to 0.526 g cm−3. The thermal conductivities under different pressures (3–105 Pa, air) and different atmospheres (N2, Ar, and CO2, 105 Pa) are investigated. The thermal conductivities are in the range of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…The SEM images of the samples are shown in Figure 4. The PBO aerogels present a three‐dimensional network porous structure is similar to the PBO aerogels in our previous research 17–18 . The morphology of PBO/SiO 2 samples is different from that of PBO aerogels with the typical three‐dimensional network structure, showing resemble flakes shape tangled together with little particles.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The SEM images of the samples are shown in Figure 4. The PBO aerogels present a three‐dimensional network porous structure is similar to the PBO aerogels in our previous research 17–18 . The morphology of PBO/SiO 2 samples is different from that of PBO aerogels with the typical three‐dimensional network structure, showing resemble flakes shape tangled together with little particles.…”
Section: Resultssupporting
confidence: 72%
“…It is synthesized through ring‐opening polymerization of benzoxazine monomer under high temperature or acid catalyst and further forming a cross‐linked three‐dimensional network structure 12–16 . In the previous study, PBO aerogels were prepared with lightweight, low thermal conductivity, 17–18 and excellent mechanical strength, 18–19 a preliminary demonstration of its potential application performance in the field of thermal insulation. Besides, PBO resin possesses self‐extinguishment and intrinsic flame retardancy because of they contain Nitrogen element and lots of Phenol rings 20–21 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the effects of the pressure on the mean molecular free path of gas and the thermal conductivity of aerogel were discussed in detail. [22] In PBZ aerogels based on Bisphenol A benzoxazine monomer, the mean free path of the gas starts to decrease, and the thermal conductivity increases rapidly when the pressure is higher than 1000 Pa. Analogous results were obtained in PBZ aerogels based on the PH-mda monomer in this article. As shown in Figure 8, the thermal conductivities of the PBZ aerogels under different pressures (10-10 5 Pa) were tested using a Hot Disk thermal constants analyzer with a pressure control device (Figure7a).…”
Section: Thermal Conductivities Of Pbz Aerogelssupporting
confidence: 78%
“…[17,18] Mahadik-Khanolkar [19] and Malakooti [20] reported that PBZ aerogels possess excellent mechanical properties and relatively low thermal conductivity. Feng [21,22] synthesized lighter PBZ aerogels with lower thermal conductivity and systematically studied their thermal conductivity. Moreover, PBZ resins possess many prominent advantages including intrinsic flame retardancy, eco-friendly synthesis process (without small-molecule release), and abundant raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ultralight porous 3D materials, with unique integral properties of ultralow density, low thermal conductivity, high porosity, and good mechanical properties, exhibit a large range of applications as absorption materials, in thermal insulation, electronic equipment, as scaffolds for tissue engineering, and stimuli‐responsive materials . Traditional inorganic aerogels, however, normally suffer from mechanical brittleness originating from rigid intrinsic quality of inorganic materials, which restricts their applications .…”
Section: Introductionmentioning
confidence: 99%